SAT-249 Polyarticular Osteoarthritis: A Disabling Manifestation of Acromegaly - Khan, Azkia (J Endocr Soc, 2020)
Background Acromegaly is a slow-onset rare endocrinopathy that is characterized by chronic overproduction of growth hormone (GH) and insulin-like growth factor-1 (IGF-1). Excess GH and IGF-1 levels lead to insulin resistance, which is implicated in most of the complications associated with acromegaly. We present a case of acromegaly, wherein the patient presented with worsening polyarthralgia and decreasing mobility. As the patient was undergoing workup for rapidly progressing osteoarthritis, the internist became suspicious of patient’s changing physical appearance. Case A 53-year-old man with medical history of diabetes mellitus and hypertension was referred to endocrine clinic on account of high IGF-1 levels, 909 ng/ml (normal: 37-245 ng/ml). He was seeking medical attention because of rapidly progressing polyarthralgia and stiffness for the last two years. His symptoms were intensifying despite use of non-steroidal anti-inflammatory drugs and intra-articular steroid injections. Imaging revealed severe degenerative changes and narrowing of joint space in bilateral hip, knee and glenohumeral joints. Internist observed that the patient was exhibiting stigmata of acromegaly such as enlargement of hands and feet, prognathism and dental space widening. Patient reported headaches, blurry vision, sleep apnea, dysphagia and right ear exostosis. Colonoscopy revealed hyperplastic polyps. Repeat IGF- 1 levels were 910 ng/ml (Normal: 37-245 ng/ml). Oral glucose tolerance test showed failure of suppression of GH. Serial GH levels were 4.50, 5.08, 6.74, 5.81 and 5.21 ng/ml (Normal: 0.01- 0.97 ng/ml). Tests for other endocrinopathies revealed the following results: serum prolactin 4 ng/ml (Normal <18 ng/ml), serum cortisol 7.9 ug/dl (Normal: 6-27 ug/dl), 24 hour urine cortisol 23mcg/24 hours (Normal: 3.5-45 mcg/24 hours), serum TSH 2.25 uIU/ml (Normal: 0.34- 3 uIU/ml), serum T4 level 0.7 ng/dl (Normal: 0.6-1.6 ng/dl) and serum T3 level 144.9ng/dl (Normal: 87-178 ng/dl). Serum total and free testosterone levels were 111 ng/dl (Normal: 240-950 ng/dl) and 3.89 ng/dl (Normal: 4.06-15.6 ng/dl) respectively and were suggestive of hypogonadism. MRI Brain showed 12x10x8mm pituitary adenoma. He was referred for transsphenoidal surgery for resection of pituitary adenoma. Conclusion Polyarticular osteoarthritis is an early manifestation of acromegaly. Systemic diseases associated with acromegaly are the primary reason for which most patients seek medical attention. It is important to look for coexisting endocrinopathies whenever the diagnosis of acromegaly is established, since mass effect of pituitary adenoma can wreak havoc on the endocrine system of the body. High index of suspicion, early diagnosis and prompt treatment are the key to reverse some but not all comorbid conditions associated with acromegaly.